Help! Somebody Get Me Out of Fourth Grade! - Winkler, Henry 1945-; Oliver, Lin; Heyer, Carol, 1950- (New York : Grosset & Dunlap, 2006)
Fearing that he may be failing fourth grade, Hank enlists the help of his friends, and even his annoying younger sister, in an effort to prevent his parents from attending a parent-teacher conference.
Reprint. Originally published: c2004.
Keywords: School stories; Fiction